Natural Dye from Kepok Banana Leaf Stalk on Cotton Fabric with Variation of Fixation - Taufik Ihsan; Sulistyo Saputro; Lina Mahardiani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
The purposes of this study are to apply the natural dye obtained from Musa paradisiaca Var. Balbisiana Colla leaf stalk on cotton fabric with variation of fixation. The experiment was carried out by several steps including extraction of natural dye, mordanting process, dyeing process, fixation process and testing the application of natural dye on cotton fabric. The application testing was evaluated based on the color fastness againts washing and rubbing, color changes with gray scale and color staining with stainning scale. The results of this study show that extract of natural dye from Musa paradisiaca Var. Balbisiana Colla leaf stalk is applicable as natural dye in textile. Moreover, using fixation can increase the color fastness in which alum 10 g/L provided the best color fastness, ie scale 3-4 (good enough) for color fastness againts washing and dry rubbing, and 4 (good) for wet rubbing.